Video documenting for language, culture and resources - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2006)
Use of video and multimedia techniques to strengthen interest in language, culture and resource management in Indonesia and Canada.